2014
DOI: 10.1186/s12884-014-0386-y
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility and potency of uterotonic drugs purchased by simulated clients in four districts in India

Abstract: BackgroundSurveillance of drug quality for antibiotics, antiretrovirals, antimalarials and vaccines is better established than surveillance for maternal health drugs in low-income countries, particularly uterotonic drugs for the prevention and treatment of postpartum hemorrhage. The objectives of this study are to: assess private sector accessibility of four drugs used for uterotonic purposes (oxytocin, methylergometrine, misoprostol, valethamate bromide); and to assess potency of oxytocin and methylergometrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…[7][8][9] The quality, efficacy and safety of oxytocin and misoprostol have been widely studied. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] Oxytocin is temperature sensitive and should therefore be stored under refrigeration at temperatures between 2°C and 8°C to prevent degradation expected at higher temperatures. 10 Degradation reduces potency and consequently the effectiveness of the medicine.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] The quality, efficacy and safety of oxytocin and misoprostol have been widely studied. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] Oxytocin is temperature sensitive and should therefore be stored under refrigeration at temperatures between 2°C and 8°C to prevent degradation expected at higher temperatures. 10 Degradation reduces potency and consequently the effectiveness of the medicine.…”
Section: Open Accessmentioning
confidence: 99%
“…[11][12][13] Some studies on the quality of oxytocin found analysed samples to contain less active pharmaceutical ingredients than was claimed in the label, while some samples also failed sterility tests. [14][15][16] LMICs with low resources may also lack facilities required for adequate storage conditions for oxytocin to ensure integrity of the product, while they may also lack trained health workers for its administration. 17 Women living among displaced populations, in conflict areas, hard to reach areas, who deliver at home or with a traditional birth attendant seldom have access to a trained health worker.…”
Section: Open Accessmentioning
confidence: 99%
“…This storage requirement can be challenging, especially in rural areas of low-and middle-income countries (LMICs) where infrastructure is poor and ambient temperatures are often high [8][9][10][11][12]. Indeed, several previous studies have shown that the quality of oxytocin, especially in LMICs, is often poor [3,[10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Лекарственные средства из группы утеротонических препаратов играют важнейшую роль в акушерстве, в частности при осуществлении родоактивации и родовозбуждения, а также в ходе профилактики и лечения ПРК. Независимо от показаний при использовании утеротонических ЛС специалисты добиваются оптимального сочетания эффективности и безопасности их применения с учетом характеристик конкретных препаратов, их дозировок, способов введения, клинических показаний и противопоказаний к их применению, а также индивидуальных особенностей пациентки [25].…”
unclassified
“…По мнению специалистов [12,13,25], в настоящее время отсутствие эффективных утеротонических препаратов является ключевым препятствием к существенному снижению материнской смертности в большинстве стран мира.…”
unclassified